الاصابة الطفيليه والبكتيرية المرافقة لالتهاب الزائده الدوديه في محافظة ذي قار - جبار نهى (University of Thi-Qar Journal of Science, 2010)
During the period from November/2008 to February/2009 to explore the prevalence of infection of parasites (Protozoa and Helminthes ) and bacterial infection causing acute appendicitis surgically removed from inpatients of Al-Hussin hospital in Nassriyia city in Thi- Qar province . The study include 68 patients with acute appendicitis of both sexes (30 male and 38 female ) . The total prevalence of parasitic infection was 39.7 % . The highest percentage of parasitic infection 27.9% was with Entamoeba histolytica and the highest percentage of bacterial infection was 34% with Escherichia coli .